3D‐Printed Cactus‐Inspired Spine Structures for Highly Efficient Water Collection. Issue 3 (17th December 2019) - Li, Xiangjia; Yang, Yang; Liu, Luyang; Chen, Yiyu; Chu, Ming; Sun, Haofan; Shan, Weitong; Chen, Yong
Abstract: The inherent fog collection mechanism used by the cactus gives inspirations for constructing energy‐efficient and environmentally friendly water collection devices. However, the related studies meet the bottleneck on improving the collection efficiency because it is hard to replicate real natural clusters of branched spines by traditional manufacturing methods. The immersed surface accumulation based 3D printing provides a tool to reproduce branched cactus spines, enabling the study of water collection of artificial spines with various designs. Here, a cactus‐inspired surface decorated with multiple directional artificial spines for highly efficient water collection and transportation is presented. The nanoscale hydrophobic coating is sputtered on the surface of the 3D‐printed spines to accelerate the water growth rate. The results show that the hexagonally arranged clusters enhance the moisture airflow around 3D‐printed spines, and the printed spines with 10° tip angle and hydrophobic coating achieve the highest weight gain of 2 mg min −1 mm −3 . This study opens intriguing perspectives for designing next‐generation structural materials with the special spatial distribution of biomimetic features to achieve energy free and highly efficient water collection. The results reported here are believed to be helpful for the development of environmental friendly water collection, water transportation, and water separation devices. Abstract : Multibranched spines inspired by cactus with the capability of water collection are produced by the immersed surface accumulation process. The hexagonally arranged spines show promising properties of water collection. It opens intriguing perspectives for designing energy‐efficient, 3D‐printed artificial water collection surfaces with unique arrangements of 3D biomimetic microstructures.